Design optimization of triple friction pendulums for base-isolated high-rise buildings. Issue 13 (October 2019) - Xu, Yanqing; Guo, Tong; Yan, Ping
The triple friction pendulum bearing, as a novel seismic isolator, has received much attention due to its notable advantages such as variable stiffness and damping; however, existing investigations and applications are mainly for low-rise or medium-rise buildings. In order to determine optimal design parameters of triple friction pendulum bearings for high-rise buildings, equations of motion for an isolated high-rise building are derived, and an evaluation function is developed to indicate the isolation effect with different pendulum parameters. In the optimization analysis, seven ground motions are scaled to three levels (corresponding to the service level, the design basis, and the maximum considered earthquakes, respectively) and the genetic algorithm is applied to determine the optimal pendulum parameters. The optimization results are compared with those obtained by the single-degree-of-freedom model, where significant difference is observed, showing the necessity of the presented study. Using the optimal parameters of triple friction pendulum bearings, seismic responses of the isolated building are analyzed and compared with those of the building isolated using the single friction pendulum bearings and the base-fixed building, where it is observed that the triple friction pendulum bearing is more effective and reliable in reducing base shear, floor acceleration, and story drifts.